Il Cimitero di Praga di Umberto Eco, romanzo delle ambiguità - Marnieri, Maria Teresa (2014)
The sixth novel by Umberto Eco is a dark journey into the mysteries of the Nineteenth Century. Following the diary of the owner of an Antiques Shop in Paris, he makes us discover the plots that changed history. Spy-story, historical novel and Gothic atmospheres are the ingredients of a difficult work that can offer many different and even contrasting interpretations. Once again we face a post-modern creation which casts a new anguishing light on events of the past that have to be deciphered and re-interpreted.